Modeling the cost-effectiveness of prolonged-release fampridine for the treatment of walking impairment in patients with multiple sclerosis in Sweden. (1st January 2021) - Acosta, Carlos; Gianinazzi, Mattia; Dort, Thibaut; Armstrong, Nigel; Ryder, Steve; Lundqvist, Thomas; Ekelund, Mats; Lycke, Jan
Abstract: Aims: To evaluate the cost-effectiveness of adding prolonged-release (PR)-fampridine to best supportive care (BSC) versus BSC alone for the improvement of walking ability in patients with MS. Methods: A cost-utility analysis based on a Markov model was developed to model responders and timed 25-foot walk (T25FW) scores, accumulated costs, and quality-adjusted life-years (QALY) in adults with MS and Expanded Disability Status Scale (EDSS) scores between 4 and 7. The analysis was conducted from a Swedish societal perspective. Results: In the base-case analysis, PR-fampridine plus BSC led to a higher QALY gain than BSC alone. The largest direct cost was professional care provision followed by hospital inpatient stays while the indirect cost was the loss of earnings due to days off work. The incremental cost-effectiveness ratio (ICER) for PR-fampridine plus BSC compared with BSC alone was 57, 109 Swedish Kronor (kr)/QALY (€5, 607/QALY [1 kr = €0.0981762 on 8 April 2021] and 6, 675/QALY [1 kr = 0.116890 on 8 April 2021]). All sensitivity analyses performed resulted in ICERs below 500, 000 kr (€49, 088 and 58, 445). Limitations: Resource use data were not specific to the Swedish market. Conclusions: PR-fampridine represents a cost-effective treatment for MS-related walking impairment in Sweden, due to improvements in patients' quality of life and reduced healthcare resource utilization.